Edukasi Penggunaan Gadget Sehat Untuk Siswa Sds Arastamar Kuala Behe Berdasarkan 1 Korintus 6:12 - Nome, Obria (Journal Of Human And Education (JAHE), 2025)
The technology of this era plays a crucial role in human life, especially for students. First and second-grade students at SDS Arastamar Kuala Behe face challenges stemming from uncontrolled use of gadgets, which disregards time and place. This issue becomes an obstacle for teachers in achieving quality education. This Community Service (PkM) initiative is a solution developed based on the volunteers' initiative. The education program was conducted using an observational method combined with sermons, discussions, and reflections at the end of each session. The volunteers used 1 Corinthians 6:12 as a foundation to guide students on healthy gadget use. This program successfully instilled an understanding that although technology provides many benefits, we must maintain control over its use to avoid disrupting other, more important activities.